From CAUR to EUR: Italian Fascism, the 'myth of Rome' and the pursuit of international primacy. (19th October 2016) - Kallis, Aristotle
ABSTRACT: The formation of Fascist Italy's international imaginary in the 1930s tells a fascinating story of growing global political ambition, of constant recalibration in the face of seismic geopolitical shifts and, in the end, a (frustrated) pursuit of symbolic primacy. Kallis discusses two different Fascist projects underpinned by this imaginary: first, the political project of internationalization promoted through instruments such as the Fasci Italiani all'Estero (Italian Fasci Abroad) and especially the Comitati d'Azione per l'Universalità di Roma (CAUR), as well as through direct diplomatic and political ties with an expanding circle of regimes in Europe and overseas; and, second, the pursuit of a deeper sense of historic-cultural primacy, linked to the idea of 'Roman universality, which became the discursive lynchpin of the ill-fated plan to host a 1942 world's fair in Rome (EUR/E42). The transformation of Fascism from a hyper-nationalist phenomenon into a force actively seeking international diffusion and finally 'universality' can be understood as a reflexive adjustment of Fascism's ideological-political horizon, driven as much by new geopolitical opportunities and frustrations as by conquering ambition and ideological continuity. In fact, Italian Fascism's trajectory from CAUR in the 1930s to EUR/E42 in the war-torn 1940s, unfolding against a backdrop of growing antagonism between Italy and Nazi Germany for global influence, retained a primary symbolic point of reference: the ideological, political and cultural-historic estate of the 'myth of Rome' as a symbolic discourse of trans-temporal and -spatial primacy.